A Panama Canal for Asia: An analysis of China's role in Cambodia and implications for international security. Issue 3 (4th May 2021) - Mohlin, Marcus
Abstract: When President Xi Jinping launched the Belt and Road Initiative in 2013 he set an enormous geopolitical change in motion. By constructing the greatest and most ambitious economic, social and physical infrastructure in world history, a massive strain on international security will follow. Because of an increased dependence on trade, this network of roads, railways and sea lanes will become of vital importance to Chinese security. There is however a problem: most of its shipping will still have to pass through the Malacca Strait, a bottleneck suitable for foreign naval blockade. To solve this, China is now looking to establish overseas dual-purpose bases.